(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2011)
The samples were preserved in 70% alcohol and plastic sleeve. 12 species were identified. Taxonomic keys were used for identification. Statistical tables were conducted that demonstrated the variety and percentage of species and infraorders. It was concluded that the population in San Cristobal island threatens the stability of the ecosystem and its species.